A socioeconomic profile of the porters in the Central Mid-Hills of Nepal - Upadhyay, Kiran Dutta (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v2i0.1069 Occasional Papers in Sociology and Anthropology Vol.2 1990 p.48-58